The Relationship Between Sleep Quality and Quality of Life Among Postmenopausal Women - Seyedeh Fatemeh Nosrati Hadiabad; Mahbubeh Abdollahi; Sayyed Majid Sadrzadeh; Fatemeh Zahra Karimi (Iran University of Medical Sciences, 2023)
Background: With increased life expectancy and changes in lifespan, now women spend more years after menopause. Women with menopausal symptoms may experience a lower quality of life (QoL) and complain about poor sleep quality. This study aimed to examine the relationship between QoL and sleep quality in postmenopausal women. Methods: This research was a predictive correlational study. The study sample was 200 postmenopausal women referred to the healthcare centers affiliated with Mashhad University of Medical Sciences in Mashhad City, Iran, in 2021. The subjects were selected through multistage cluster sampling. To assess the quality of sleep and life quality, the Pittsburgh Sleep Quality Index (PSQI) and Menopause-Specific QoL questionnaire (MENQOL) were used. The obtained data were analyzed by the Pearson correlation coefficient and multiple linear regression in SPSS software, version 21. The significance level was set at P<0.05. Results: The mean±SD age of the subjects was 53.92±6.13 years. Their mean±SD scores of sleep quality and QoL were 48.62±21.98 and 4.93±2.74, respectively, and 37% of women had sleep disorders. The multiple determination coefficient for the linear regression model was equal to 0.35, and there was a significant direct relationship between sleep quality and QoL (b=3.72, 95% CI =2.70-4.74, P<0.001). So for each unit change in sleep quality, the average QoL score increased by 3.72 units. Conclusion: Considering the relationship between sleep quality and QoL in postmenopausal women, it is recommended that these women use appropriate methods to improve sleep quality. Also, health professionals should keep this issue in mind when examining the health status of this group of women.